Impact of sea level rise on current and wave in Van Uc coastal area - Hai, Nguyen Minh; Vinh, Vu Duy; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents the results of analysis, comparison of some characteristics of current, wave at Van Uc estuary area when being affected by sea level rise due to climate change based on Delft3D model. Scenario groups are established: The current scenario and the scenarios simulating effect of sea level rise 0.5 m and 1.0 m. The results of calculation and simulation show that the velocity values change locally when sea level rises: Rise in the northern and southern areas (0.2–5 cm/s); decrease in the navigation channel (0.6–30 cm/s). Sea level rise causes the increase of wave height in the coastal area (13.5–43.8% in the dry season and 20–40% in the rainy season) and fewer changes in the outer area.